2014
DOI: 10.2147/ijn.s63095
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal closure reinforcement by using polypropylene mesh functionalized with poly-Ԑ-caprolactone nanofibers and growth factors for prevention of incisional hernia formation

Abstract: Incisional hernia affects up to 20% of patients after abdominal surgery. Unlike other types of hernia, its prognosis is poor, and patients suffer from recurrence within 10 years of the operation. Currently used hernia-repair meshes do not guarantee success, but only extend the recurrence-free period by about 5 years. Most of them are nonresorbable, and these implants can lead to many complications that are in some cases life-threatening. Electrospun nanofibers of various polymers have been used as tissue scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 40 publications
1
53
0
Order By: Relevance
“…51 Previous studies have mentioned various drug-delivery systems based on a PCL composite scaffold successfully used for hernia regeneration. 29,44,45 PCL nanofibers were used in our study as a carrier of GFs gradually released from platelets adhered to the nanofiber surface, with the aim of using the material in hernia regeneration. The use of this system enabled us to avoid the complications caused by a burst release of high doses of GFs.…”
Section: Absorbance (Au)mentioning
confidence: 99%
See 3 more Smart Citations
“…51 Previous studies have mentioned various drug-delivery systems based on a PCL composite scaffold successfully used for hernia regeneration. 29,44,45 PCL nanofibers were used in our study as a carrier of GFs gradually released from platelets adhered to the nanofiber surface, with the aim of using the material in hernia regeneration. The use of this system enabled us to avoid the complications caused by a burst release of high doses of GFs.…”
Section: Absorbance (Au)mentioning
confidence: 99%
“…Our previous study proved the suitability of a composite scaffold based on PCL nanofibers deposited on a PP mesh for hernia regeneration in rabbits. 29 A histological and biomechanical evaluation revealed PCL nanofibers had better healing capacity than conventional PP mesh for preventing hernia formation. 29 In the present study, we tested a new composite scaffold based on a PP surgical mesh, PCL nanofibers, and adhered thrombocytes.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, these films are often used as adhesion barrier layers and have no direct interaction with the hernia site [5]. Conversely, it has been demonstrated that resorbable nanofiber layers in direct contact with the hernia site promote collagen deposition and remodeling, and yield better mechanical properties at the wound interface compared to polypropylene mesh alone [21]. This suggests that if the adhesion barrier layer was made from nanofibers instead of a film, there would be a significantly lower inflammatory response.…”
Section: Discussionmentioning
confidence: 99%